Unraveling the Alkaline Phosphatase Inhibition, Anticancer, and Antileishmanial Potential of Coumarin–Triazolothiadiazine Hybrids: Design, Synthesis, and Molecular Docking Analysis. Issue 7 (23rd May 2016) - Ibrar, Aliya; Zaib, Sumera; Jabeen, Farukh; Iqbal, Jamshed; Saeed, Aamer
Abstract : A series of new coumarin–triazolothiadiazine hybrid compounds (5a –j ) was designed and synthesized by using the molecular hybridization concept. The cyclocondensation reaction involves the coumarinyl 4‐amino‐1, 2, 4‐triazole and a range of bromo‐acetophenones, delivering the desired products in good yields. The structures of the synthesized compounds were established on the basis of spectro‐analytical data. The prepared compounds were evaluated against alkaline phosphatase (ALP) where compound5j incorporating bis‐coumarinyl motifs at the 3‐ and 6‐positions of the heteroaromatic core turned out to be a potent inhibitor with an IC50 value of 1.15 ± 1.0 µM. The synthesized compounds were also tested against Leishmania major and5h was the lead member with an IC50 value of 0.89 ± 0.08 μM. Anticancer activity was also determined using kidney fibroblast (BHK‐21) and lung carcinoma (H‐157) cancer cell lines. Compound5i showed highest cytotoxic potential against H‐157 cells with an IC50 value of 1.01 ± 0.12 μM, which is an improved inhibition compared to the standards (vincristine and cisplatin) used in this assay. Molecular docking studies were carried out on the synthesized library of coumarin–triazolothiadiazine hybrids against ALP. Almost all of the compounds showed strong interactions with the key residues of the active site of the receptor. In case of compounds5a –c, 5h, and5j, docking results positively complemented the experimental screening. These results provided substantial evidence for the further development of these compounds as potent inhibitors of ALP. Abstract : A molecular hybridization approach provided access to a new series of cytotoxic coumarin–triazolothiadiazine hybrids as promising inhibitors of alkaline phosphatase and leishmaniasis.